The effect of dicarbonyl stress on the development of kidney dysfunction in metabolic syndrome - a transcriptomic and proteomic approach - Markova, Irena; Hüttl, Martina; Oliyarnyk, Olena; Kacerova, Tereza; Haluzik, Martin; Kacer, Petr; Seda, Ondrej; Malinska, Hana (Nutrition & metabolism, 2019)
BACKGROUND AND AIMS: Dicarbonyl stress plays an important role in the pathogenesis of microvascular complications that precede the formation of advanced glycation end products, and contributes to the development of renal dysfunction. In renal cells, toxic metabolites like methylglyoxal lead to mitochondrial dysfunction and protein structure modifications.In our study, we investigated the effect of methylglyoxal on metabolic, transcriptomic, metabolomic and proteomic profiles in the context of the development of kidney impairment in the model of metabolic syndrome. MATERIALS AND METHODS: Dicarbonyl stress was induced by intragastric administration of methylglyoxal (0.5 mg/kg bw for 4 weeks) in a strain of hereditary hypertriglyceridaemic rats with insulin resistance and fatty liver. RESULTS: Methylglyoxal administration aggravated glucose intolerance (AUC0-120 p < 0.05), and increased plasma glucose (p < 0.01) and insulin (p < 0.05). Compared to controls, methylglyoxal-treated rats exhibited microalbuminuria (p < 0.01). Targeted proteomic analysis revealed increases in urinary secretion of pro-inflammatory parameters (MCP-1, IL-6, IL-8), specific collagen IV fragments and extracellular matrix proteins. Urine metabolomic biomarkers in methylglyoxal-treated rats were mainly associated with impairment of membrane phospholipids (8-isoprostane, 4-hydroxynonenal).Decreased levels of glutathione (p < 0.01) together with diminished activity of glutathione-dependent antioxidant enzymes contributed to oxidative and dicarbonyl stress. Methylglyoxal administration elevated glyoxalase 1 expression (p < 0.05), involved in methylglyoxal degradation. Based on comparative transcriptomic analysis of the kidney cortex, 96 genes were identified as differentially expressed (FDR < 0.05). Network analysis revealed an over-representation of genes related to oxidative stress and pro-inflammatory signalling pathways as well as an inhibition of angiogenesis suggesting its contribution to renal fibrosis. CONCLUSION: Our results support the hypothesis that dicarbonyl stress plays a key role in renal microvascular complications. At the transcriptome level, methylglyoxal activated oxidative and pro-inflammatory pathways and inhibited angiogenesis. These effects were further supported by the results of urinary proteomic and metabolomic analyses.
Keywords: Methylglyoxal; Microvascular complications; Kidney dysfunction; Transcriptomics; Proteomics; Metabolic syndrome; Metabolomics